Nearly 30 years of SHELA foundation: An undoubtful feat Education: between hell and backwater, two intermittent realities - Vera de Flachs, María Cristina; Martinez Moya, Armando (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Echoes of a difficult environmentLike two concentric circles, realities confront each other, splash each other, develop their life path and seem to concentrate on their environment. One of them is education and the whole world that surrounds it in our vast Latin American continent. It registers its evolution with multiple faces; it is enveloped by a veil of humanism, starting from the palpitations of the noble exercise of teaching and learning, whether in the environments of the world of children or youth or in the fields of the work of higher education. The teaching lineage in its noble daily work. The other reality is the terrible environment in which we live in 2023, the war with its criminal face, but also social and domestic violence, references that not only hurt and outrage, because domestic violence and child abuse splash the walls and enter the school when they break into the behavior of students and, sometimes, exert symbolic violence on children and adolescents.Coexisting with the curricular routine that marks the generous work of our Latin American teachers, we hear the echoes of the Russian invasion of Ukraine, and with it, the heart-rending speeches of the industrialized countries that advocate with their false ethics for that conflagration, while they continue to feed with millions of dollars the NATO war machine. And now, in these last months, we are terrified to see how terrorism reappears and behind it, the Israeli genocide on Palestinian children and families. As educators, we cannot remain silent.